Planting a seed: Sustainable education for students with Additional Support Needs - Don MacKeen (European Journal of Geography)
Realities of climate change make meeting Sustainable Development Goals even more urgent, not least in terms of education. In Scotland's Curriculum for Excellence (CfE) these goals are promoted in the Learning for Sustainability initiative which aims to embed sustainability in education. While inclusion is claimed to be a non-negotiable aspect of CfE, the reality is that for many students with Additional Support Needs (ASN) (in Scottish education this term has superseded Special Educational Needs), access to a high-quality education is limited. This paper looks at a case study where urban gardening is used as a teaching tool for students with ASN. The City Works programme has grown out of nearly twenty years of work with ASN students, using urban gardening as a vehicle for developing citizenship, groupwork skills and a greater understanding of sustainability. Staff, students, and community gardeners were interviewed to ascertain their experience of the project and the value of a sustainable and inclusive education are discussed. Finally, it is argued that this educational approach should be developed further, in coordination with other educational professionals.